Expression of Olig2, Nestin, NogoA and AQP4 have no impact on overall survival in IDH-wildtype glioblastoma - Behling, Felix (PLoS One, 2020)
Despite many years of research efforts and clinical trials the prognosis of patients diagnosed with glioblastoma remains very poor. The oligodendrocyte transcription factor 2 (Olig2) was identified as a marker for glioma stem cells, which are believed to be responsible for glioma recurrence and therapy resistance. In this retrospective analysis we assessed the prognostic value of oligodendroglial and glioma stem cell markers in 113 IDH-wildtype glioblastomas. Immunohistochemical staining for Olig2, NogoA, AQP4 and Nestin was performed in combination with sequencing of IDH1 and IDH2 as well as promotor methylation analysis of the MGMT gene. Even though differences in overall survival according to Olig2 expression were observed, univariate and multivariate survival analysis did not reveal a firm significant prognostic impact of Olig2, NogoA, AQP4 or Nestin expression. Additionally, no differences in the expression of these markers depending on clinical status, age or gender were found. The established independent prognostic factors age<65, Karnofsky Performance Status> = 70 and methylated MGMT gene promoter were significant in the multivariate analysis. In conclusion expression of oligodendroglial and glioma stem cell markers do not have an independent prognostic effect in IDH-wildtype glioblastoma.